Surface modification of polypropylene surgical meshes for improving adhesion with poloxamine hydrogel adhesive. Issue 4 (29th September 2018) - Lu, Xinyue; Khanna, Astha; Luzinov, Igor; Nagatomi, Jiro; Harman, Melinda
Abstract: Tissue adhesive has notable clinical benefits in hernia repair fixation. A novel poloxamine tissue adhesive was previously shown to successfully bond collagen tissue with adequate adhesive strength. In application related to attachment of polypropylene (PP) mesh, the adhesive strength between the mesh and poloxamine hydrogel adhesive is limited by the hydrophobicity of PP monofilaments and lack of covalent bond formation. The purpose of this study was to compare two different surface modifications [bovine serum albumin (BSA) adsorption and poly‐glycidyl methacrylate/human serum albumin (PGMA/HSA) grafting] of PP mesh for improving the adhesive strength between poloxamine hydrogel adhesive and PP mesh. The PGMA/HSA surface modification significantly improved the adhesive strength for meshes attached with poloxamine hydrogel tissue adhesive compared with unmodified meshes and meshes modified by BSA adsorption. An area of 1 cm 2 adhesive provided for a maximum adhesive strength of 65–70 kPa for meshes modified by PGMA/HSA, 4–13 kPa for meshes modified by BSA, and 22–45 kPa for unmodified meshes. Optical microscopy and infrared spectroscopy (FTIR) confirmed the improved adhesive strength was achieved through mechanical interlock of the hydrogel tissue adhesive into the PP mesh pores and chemical bonding of the albumin after successful PGMA/HSA grafting onto the PP monofilaments. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1047–1055, 2019.